Aromatic or Hetero-aromatic Directly Attached Tri and Tetrasubstituted Methanes: New Chemical Entities as Anti-Infectives - Roy, Deblina; Thakare, Ritesh P.; Chopra, Sidharth; Panda, Gautam (Current Medicinal Chemistry, 2023)
Tri and Tetra-substituted Methanes (TRSMs) are a significant structural motif in many approved drugs and prodrugs. There is increasing use of TRSM units in medicinal chemistry, and many derivatives are specifically designed to make drug–target interactions through new chemical space around TRSM moiety. In this perspective, we describe synthetic challenges for accessing a range of functionalized selective TRSMs and their molecular mechanism of action, especially as anti-infectives. Natural anti-infectives like (+)-Bionectin A, B, (+)-Gliocladine C, Balanocarpol having TRSMs selectively and effectively bind to target proteins in comparison to planar motif having more sp2 carbons perhaps due to conformation which reduces the penalty for conformational entropy with the enhancement of three-dimensionality. Properties of repurposed TRSMs like Almitrine, Ifenprodil, Baricitinib and Remdesivir with their recent progress in COVID-19 therapeutics with their mode of action are also delineated. This perspective is expected to deliver a user guide and reference source for scientists, researchers and academicians in pursuing newly designed TRSMs as therapeutics.
Keywords: baricitinib and remdesivir